Moderate effectiveness of multiple-use protected areas as a policy tool for land conservation in Atlantic Spain in the past 30 years - Rodriguez-Rodriguez, David; Ruiz-Sinoga, José Damián (Elsevier Ltd., 2021)
Protected areas (PAs) are the main global policy instrument to avert the current biodiversity crisis by conserving important species and habitats on site. Yet important pressures around PAs and in PAs, notably land use-land cover (LULC) changes, jeopardise the conservation role of these tools. In Spain, as well as in most developed countries, land development is the main pressure on its rich biodiversity. Here, we used a semi-experimental Before-After-Control-Impact (BACI) research design with covariates to ascertain whether three categories of multiple-use PAs including Nature Parks, Sites of Community Importance (SCIs) and Special Protection Areas (SPAs) have been effective to prevent land development in Atlantic Spain between 1987 and 2017 using CORINE Land Cover (CLC) data. We split our census sample of PAs according to two geographic zones: coastal zone and inland zone, and four administrative sub-zones (regions with distinctive governance systems): Galicia, Asturias, Cantabria and the Basque Country. We created and tested the validity of three types of controls specific to each PA category: standard 5-km buffer controls, bio-physically adjusted standard controls, and bio-physically adjusted random controls across zones. Multiple-use PAs reduced, though not completely avoided, land development in all zones and sub-zones compared with controls. An effectiveness gradient among PA categories was apparent: NPs ≥ SCIs > SPAs. Coastal areas, both protected and unprotected, experienced greater land development rates than inland areas, with coastal SPAs showing poor effectiveness results. The Basque Country was the best-performing region regarding PA effectiveness, with the remaining regions showing similar PA performance results regardless of the prevailing political party in power for most of the study period. Random controls had the greatest bio-physical similarity to their cases and produced larger control areas than standard buffer controls.
Keywords: Suelo - Uso; Espacios naturales protegidos; Land development; Natura 2000; Performance; Coast; Inland; Europe